2014
DOI: 10.1177/1060028014549185
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Acute Kidney Injury in Children Receiving Vancomycin

Abstract: AKI was common in children receiving vancomycin. Higher doses of vancomycin were associated with increased odds of AKI. The risks and benefits of higher vancomycin dosing should be considered for each patient. Patients should be monitored closely for AKI, especially with higher doses, extended durations of therapy, or concomitant use of nephrotoxic medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 44 publications
6
69
4
Order By: Relevance
“…While we found that 23.4% of our study population developed AKI (any category), the frequency of pRIFLE category I and F (5.3%) was slightly lower than previously reported rates of pRIFLE category I in the PICU. 7,9 Totapally et al 7 and Sinclair et al 9 found that 17.2% and 13.7% of patients developed pRIFLE category I, respectively, which is threefold greater than our result of 5.3% that developed either category I or F. This may be due to the fact that our study did not include repeat courses of vancomycin for individual patients. 7 Our results on concomitant risk factors are overall similar to the results in the current literature.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…While we found that 23.4% of our study population developed AKI (any category), the frequency of pRIFLE category I and F (5.3%) was slightly lower than previously reported rates of pRIFLE category I in the PICU. 7,9 Totapally et al 7 and Sinclair et al 9 found that 17.2% and 13.7% of patients developed pRIFLE category I, respectively, which is threefold greater than our result of 5.3% that developed either category I or F. This may be due to the fact that our study did not include repeat courses of vancomycin for individual patients. 7 Our results on concomitant risk factors are overall similar to the results in the current literature.…”
Section: Discussioncontrasting
confidence: 55%
“…Conversely, Totapally et al 7 did not find any association between trough concentrations and AKI. Interestingly, Sinclair et al 9 did not include trough concentrations in their multiple logistic regression analysis, but maximum troughs were significantly higher in patients who developed AKI.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations